Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

Antiseizure medication and perceived “fair” cost allocation: A factorial survey among neurologists, persons with epilepsy, their relatives, and a control group - Stritzelberger, Jenny; Walther, Katrin; Olmes, David; Gollwitzer, Stefanie; Graf, Wolfgang; Welte, Tamara; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Kriwy, Peter; Hamer, Hajo (Epilepsia, 2022)
Objective: Because resources are limited in modern health care systems, the decision on the allocation of expensive drugs can be supported by a public consent. This study examines how various factors influence subjectively perceived “fair” pricing of antiseizure medication (ASM) among four groups including physicians, persons with epilepsy (PWEs), their relatives, and a control group. Methods: We conducted a factorial survey. Vignettes featured a fictional PWE receiving a fictional ASM. The characteristics of the fictional PWE, ASM, and epilepsy varied. Participants were asked to assess the subjectively appropriate annual cost of ASM treatment per year for each scenario. Results: Fifty-seven PWEs (mean age (SD) 37.7 ± 12.3, 45.6% female), 44 relatives (age 48.4 ± 15.7, 51.1% female), 46 neurologists (age 37.1 ± 9.6, 65.2% female), and 47 persons in the control group (age 31.2 ± 11.2, 68.1% female) completed the questionnaire. The amount of money that respondents were willing to spend for ASM treatment was higher than currently needed in Germany and increased with disease severity among all groups. All groups except for PWEs accepted higher costs of a drug with better seizure control. Physicians and the control group, but not PWEs and their relatives, tended to do so also for minor or no side effects. Physicians reduced the costs for unemployed patients and the control group spent less money for older patients. Significance: ASM effectiveness appears to justify higher costs. However, the control group attributed less money to older PWEs and physicians allocated fewer drug costs to unemployed PWEs.
CRIS-Team Scopus Importer:2022-08-19

Anti-seizure medication is not associated with an increased risk to develop cancer in epilepsy patients - Stritzelberger, Jenny; Lang, Johannes; Mueller, Tamara M.; Reindl, Caroline; Westermayer, Vivien; Kostev, Karel; Hamer, Hajo (Journal of Neurology, 2021)
Objective: Whether anti-seizure medication (ASM) increases the risk for cancer has been debated for decades. While for some ASM, a carcinoma-promoting effect has been suspected, carcinoma-protective effects have been shown for other ASM. However, the issue remains unresolved as data from preclinical and clinical studies have been inconsistent and contradictory. Methods: We collected anonymous patient data from practice neurologists throughout Germany between 2009 and 2018 using the IMS Disease Analyzer database (QuintilesIMS, Frankfurt, Germany). People with epilepsy (PWE) with an initial cancer diagnosis and antiepileptic therapy prior to the index date were 1:1 matched with a control group of PWE without cancer according to age, gender, index year, Charlson Comorbidity Index, and treating physician. For both groups, the risk to develop cancer under treatment with different ASMs was analyzed using three different models (ever use vs. never use (I), effect per one (II) and per five therapy years (III). Results: A total of 3152 PWE were included (each group, n = 1,576; age = 67.3 ± 14.0 years). The risk to develop cancer was not significantly elevated for any ASM. Carbamazepine was associated with a decreased cancer risk (OR Model I: 0.699, p <.0001, OR Model II: 0.952, p =.4878, OR Model III: 0.758, p <.0004). Significance: Our findings suggest that ASM use does not increase the risk of cancer in epilepsy patients.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiseizure medication; Carbamazepine; Carcinogenicity; Epilepsy

Assessing comfort in the epilepsy monitoring unit: Psychometric testing of an instrument - Egger-Rainer, Andrea; Trinka, Eugen; Zimmermann, Georg; Arnold, Stephan; Boßelmann, Christian; Hamer, Hajo; Hengsberger, Anna; Lang, Johannes; Lerche, Holger; Noachtar, Soheyl; Pataraia, Ekaterina; Schulze-Bonhage, Andreas; et al. (Epilepsy & Behavior, 2020)
Purpose: The purpose of the study was to evaluate the psychometric properties of the newly developed Epilepsy Monitoring Unit Comfort Questionnaire (EMUCQ) according to the consensus-based standards for the selection of health measurements instruments (COSMIN). Moreover, we aimed to assess changes in comfort-levels. Methods: From October 2018 to November 2019, a total of 267 patients participated in a quantitative study in ten epilepsy centers in Austria and southern Germany. For basic item analysis, descriptive analysis and correlational analysis were computed. An exploratory factor analysis (EFA) was undertaken to detect the factor structure. Reliability was checked through internal consistency (Cronbach's alpha) and the measurement error. In the validity domain, convergent validity and structural validity were estimated. t-Tests were used to detect changes in comfort-levels. Results: Due to unfavorable statistical properties, two items were removed. Exploratory factor analysis showed a three-factorial solution. The EMUCQ was found to be a reliable instrument (Cronbach's alpha 0.77–0.81 for the subscales, 0.88 for the scale total comfort); convergent validity could be supported, too. Confirmatory factor analysis (CFA) supported the hypothesis that structural validity for the three subscales holds. The patients' comfort levels were lower at the end of the stay than at the beginning and lower in nonseizure-free patients compared with seizure-free patients. Conclusion: Validity and reliability are supported for the 42-item EMUCQ in the three-factorial solution. Owing to the item reduction and modifications made in the CFA, a new test should be carried out on a different sample.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Comfort; Epilepsy monitoring unit; Questionnaire; Validation study

Association of interictal epileptiform discharges and serum concentration of levetiracetam and lamotrigine - Lang, Johannes; Willno, Alexander; Reindl, Caroline; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Walther, Katrin; Hamer, Hajo (Frontiers in Neurology, 2024)
Background: Interictal epileptiform discharges (IEDs) are an electrographic biomarker of epilepsy. Despite their crucial role in diagnosing epilepsy, heterogeneous findings exist on the mechanisms underlying their occurrence and the effects of anti-seizure medications (ASMs) on IEDs. Methods: We conducted a study to investigate the association between IED frequency and the serum concentration of two commonly used ASMs, levetiracetam (LEV) and lamotrigine (LTG). We included 56 patients undergoing a continuous video EEG monitoring in our center with tapering of ASM. IED frequency was analyzed using automated and semiautomated methods and serum samples were collected sequentially throughout the stay. Results: The cohort consisted of 41 patients (23 female, 18 male), between 19 and 64 years (mean 37.42 years), most of which were diagnosed with focal epilepsy (93%). IED frequency increased after ASM reduction revealing a negative correlation similarly with LEV and LTG serum concentrations (p = 0.0057 and p = 0.0426, respectively). Discussion: Notably, we observed a significant increase in IED frequency following dose reduction or discontinuation of both medications. This effect was reversed after ASM were re-dosed. This may indicate the suppressive properties of LEV and LTG against epileptic seizures. Furthermore, our study highlights the importance of ASM discontinuation, which may be required for capturing IEDs during diagnostic continuous EEG monitoring, and not be fully explained by circadian or ultradian rhythms alone. Conclusion: Our findings contribute to the understanding of ASM effects on IED frequency dynamics and suggest seizure suppressive properties of LEV and LTG.
CRIS-Team Scopus Importer:2025-04-01
Keywords: anti-seizure medication; anticonvulsants; antiepileptic drugs; interictal epileptiform discharges; spikes

Attitudes toward persons with epilepsy as friends: Results of a factorial survey - Walther, Katrin; Kriwy, Peter; Stritzelberger, Jenny; Graf, Wolfgang; Gollwitzer, Stefanie; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Welte, Tamara; Hamer, Hajo (Epilepsia, 2023)
Objective: Discrimination against persons with epilepsy (PWEs) may persist. The aim of this study was to examine whether epilepsy is an obstacle to desired friendship.Methods: A factorial survey (vignettes), which is less biased by social desirability, was applied to PWEs, their relatives, and lay persons. The vignettes described a person who was varied by the dimensions of age (younger, same age, older), gender (male, female), disease (healthy, mild epilepsy, severe epilepsy [generalized toni-clonic seizures], diabetes), origin (German, non-German), contact (phone/internet, activities at home, activities outside), frequency of contacts (weekly, monthly), and distance (around the corner, 10 km away). Respondents rated their willingness to befriend the person on a 10-point Likert scale. Multivariate regression determined the contribution of each dimension on the judgment.Results: Participants were 64 PWEs (age = 37.1 +/- 14.0 years), 64 relatives of PWEs (age = 45.1 +/- 13.6 years), and 98 controls without contact with PWEs (age = 24.4 +/- 10.1 years). Controls were less interested in a friendship with a PWE with mild epilepsy (-3.4%) and even more avoided PWEs with severe epilepsy (-11.7%), whereas in PWEs with toni-clonic seizures, a mild form of epilepsy was actually conducive to friendship (+7.0%). Controls preferred females (+5.0%) and disliked younger people (-12.3%) and contacts via the internet or telephone (-7.3%). PWEs were also less interested in younger people (-5.8%), and relatives of PWEs had a lower preference for friendships with longer distance (-2.3%).Significance: PWEs still suffer from a risk of social avoidance, and this becomes more evident with generalized motor seizures.
CRIS-Team WoS Importer:2023-02-03

Berthold Kihn und das Kihnsche Pulver: Über ein vergessenes Therapeutikum in seinem problematischen historischen Kontext - Kasper, Burkhard; Graf, Wolfgang; Lang, Johannes; Krämer, Günter (Zeitschrift für Epileptologie, 2021)
Berthold Kihn (1895–1964) was a German psychiatrist. This article describes his life and works with respect to his contributions to the treatment of epilepsy, for which he invented and broadly used his own pharmaceutical treatment, Kihn’s powder. Particular attention is paid to an overt discrepancy in Kihnʼs actions when comparing his later and earlier career years, when he was a National Socialism ideologist and not only an advocate of sterilization and so-called euthanasia but also an active protagonist during the Nazi regime.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Aktion T4; Epilepsy; Erlangen; Euthanasia; Kihn

Defining benchmark outcomes for mesial temporal lobe epilepsy surgery: A global multicenter analysis of 1119 cases - Drexler, Richard; Ricklefs, Franz L.; Ben-Haim, Sharona; Rada, Anna; Wörmann, Friedrich; Cloppenborg, Thomas; Bien, Christian G.; Simon, Matthias; Kalbhenn, Thilo; Colon, Albert; Rijkers, Kim; Schijns, Olaf; et al. (Epilepsia, 2024)
Objective: Benchmarking has been proposed to reflect surgical quality and represents the highest standard reference values for desirable results. We sought to determine benchmark outcomes in patients after surgery for drug-resistant mesial temporal lobe epilepsy (MTLE). Methods: This retrospective multicenter study included patients who underwent MTLE surgery at 19 expert centers on five continents. Benchmarks were defined for 15 endpoints covering surgery and epilepsy outcome at discharge, 1 year after surgery, and the last available follow-up. Patients were risk-stratified by applying outcome-relevant comorbidities, and benchmarks were calculated for low-risk (“benchmark”) cases. Respective measures were derived from the median value at each center, and the 75th percentile was considered the benchmark cutoff. Results: A total of 1119 patients with a mean age (range) of 36.7 (1–74) years and a male-to-female ratio of 1:1.1 were included. Most patients (59.2%) underwent anterior temporal lobe resection with amygdalohippocampectomy. The overall rate of complications or neurological deficits was 14.4%, with no in-hospital death. After risk stratification, 377 (33.7%) benchmark cases of 1119 patients were identified, representing 13.6%–72.9% of cases per center and leaving 742 patients in the high-risk cohort. Benchmark cutoffs for any complication, clinically apparent stroke, and reoperation rate at discharge were ≤24.6%, ≤.5%, and ≤3.9%, respectively. A favorable seizure outcome (defined as International League Against Epilepsy class I and II) was reached in 83.6% at 1 year and 79.0% at the last follow-up in benchmark cases, leading to benchmark cutoffs of ≥75.2% (1-year follow-up) and ≥69.5% (mean follow-up of 39.0 months). Significance: This study presents internationally applicable benchmark outcomes for the efficacy and safety of MTLE surgery. It may allow for comparison between centers, patient registries, and novel surgical and interventional techniques.
CRIS-Team Scopus Importer:2024-03-15
Keywords: benchmarking; neurosurgery; outcome; quality; seizure

DIGITALLY ENHANCED TREAT-TO-TARGET AND SHARED DECISION-MAKING APPROACH WITH A DIGITAL HEALTH APPLICATION: INTERIM RESULTS FROM A RANDOMIZED CONTROLLED TRIAL - Knitza, Johannes; Grahammer, M.; Böltz, Sebastian; Lang, Johannes; Detert, M.; Bader, M.; Kleyer, Arnd; Simon, David; Kronke, G.; Schett, Georg; Detert, J. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Do all patients in the epilepsy monitoring unit experience the same level of comfort? A quantitative exploratory secondary analysis - Egger-Rainer, Andrea; Hettegger, Sophie Martina; Feldner, Raphael; Arnold, Stephan; Bosselmann, Christian; Hamer, Hajo; Hengsberger, Anna; Lang, Johannes; Lorenzl, Stefan; Lerche, Holger; Noachtar, Soheyl; Pataraia, Ekaterina; et al. (Journal of Advanced Nursing, 2021)
Aims To find out which variables may be associated with comfort of patients in an epilepsy monitoring unit. Design Exploratory, quantitative study design. Methods Data were collected from October 2018 to November 2019 in Austria and Southern Germany. A total of 267 patients of 10 epilepsy centres completed the Epilepsy Monitoring Unit Comfort Questionnaire which is based on Kolcaba's General Comfort Questionnaire. Secondary data analysis were conducted by using descriptive statistics and an exploratory model building approach, including different linear regression models and several sensitivity analyses. Results Total comfort scores ranged from 83 to 235 points. Gender, occupation and centre turned out to be possible influential variables. On average, women had a total comfort score 4.69 points higher than men, and retired persons 28.2 points higher than high school students >= 18 years. Comfort scores of younger patients were lower than those of older patients. However, age did not show a statistically significant effect. The same could be observed in marital status and educational levels. Conclusion When implementing comfort measures, nurses must be aware of variables which could influence the intervention negatively. Especially, high school students >= 18 years should be supported by epilepsy specialist nurses, in order to reduce uncertainty, anxiety and discomfort. But, since the identified variables account only for a small proportion of the inter-individual variability in comfort scores, further studies are needed to find out additional relevant aspects and to examine centre-specific effects more closely. Impact Nurses ensure patient comfort during a hospital stay. However, there are variables that may impair the effectiveness of the nursing measures. Our study showed that the experience of comfort was highly individual and could be explained by sociodemographic variables only to a limited extent. Nurses must be aware that additional factors, such as the situation in the individual setting, may be relevant.
CRIS-Team WoS Importer:2021-12-03

Enhancing Safety in Epilepsy Surgery (EASINESS): Study Protocol for a Retrospective, Multicenter, Open Registry - Drexler, Richard; Ben-Haim, Sharona; Bien, Christian G.; Borger, Valeri; Cardinale, Francesco; Carpentier, Alexandre; Cendes, Fernando; Chandra, Sarat; Clusmann, Hans; Colon, Albert; Curtis, Marco De; Delev, Daniel; et al. (Frontiers in Neurology, 2021)
Introduction: Optimizing patient safety and quality improvement is increasingly important in surgery. Benchmarks and clinical quality registries are being developed to assess the best achievable results for several surgical procedures and reduce unwarranted variation between different centers. However, there is no clinical database from international centers for establishing standardized reference values of patients undergoing surgery for mesial temporal lobe epilepsy. Design: The Enhancing Safety in Epilepsy Surgery (EASINESS) study is a retrospectively conducted, multicenter, open registry. All patients undergoing mesial temporal lobe epilepsy surgery in participating centers between January 2015 and December 2019 are included in this study. The patient characteristics, preoperative diagnostic tools, surgical data, postoperative complications, and long-term seizure outcomes are recorded. Outcomes: The collected data will be used for establishing standardized reference values ("benchmarks") for this type of surgical procedure. The primary endpoints include seizure outcomes according to the International League Against Epilepsy (ILAE) classification and defined postoperative complications. Discussion: The EASINESS will define robust and standardized outcome references after amygdalohippocampectomy for temporal lobe epilepsy. After the successful definition of benchmarks from an international cohort of renowned centers, these data will serve as reference values for the evaluation of novel surgical techniques and comparisons among centers for future clinical trials. Clinical Trial Registration:This study is indexed at clinicaltrials.gov (NT 04952298).
CRIS-Team WoS Importer:2022-01-28

Epidemiology of epilepsy in old age – English Version Epidemiologie der Epilepsie im höheren Lebensalter – Englische Version - Lang, Johannes; Hamer, Hajo (Zeitschrift für Epileptologie, 2022)
Background: Epilepsy is a common neurological disease affecting all ages. The increasing frequency of symptomatic epilepsies with age is partly due to cerebrovascular and neurodegenerative diseases. Better knowledge of the epidemiology of epilepsy in old age improves our understanding of the disease as well as the therapeutic and sociomedical challenges for the individual and society. Objective: What do we currently know about the epidemiology of the epilepsies in old age and how should this be classified? Material and methods: A MEDLINE search in PubMed was conducted using the terms “epilepsy”, “elderly” and “incidence” or “prevalence” or “epidemiology” and relevant publications were analyzed. Results: The point prevalence of epilepsy of older age is 0.5–0.8% of the population and affects approximately 500,000 people in Germany. The highest age-adjusted prevalence is reported to lie beyond the age of 75 years. In recent decades, the prevalence climbed further among the 75-year-olds to be twice as high as among the adult working population. The incidence shows a significant increase among patients 65 years and older, reaches its maximum at around 80–85 years of age and is somewhat higher in men. Conclusion: Reasons for the high incidence and prevalence of epilepsy in old age are the age-related incidence of potentially epilepsy-associated diseases combined with a longer long-term survival for these diseases due to better medical care and an increase in life expectancy. The change in the age pyramid with a higher (and in the coming decades further increasing) proportion of old people, will further increase the rise of epilepsy of older age.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aged; Elderly; Incidence; Prevalence; Seizures

Epidemiology of epilepsy in old age. German version Epidemiologie der Epilepsie im höheren Lebensalter - Lang, Johannes; Hamer, Hajo (Zeitschrift für Epileptologie, 2022)
Background: Epilepsy is a common neurological disease affecting all ages. The increasing frequency of symptomatic epilepsies with age is partly due to cerebrovascular and neurodegenerative diseases. Better knowledge of the epidemiology of epilepsy in old age improves our understanding of the disease as well as the therapeutic and sociomedical challenges for the individual and society. Objective: What do we currently know about the epidemiology of the epilepsies in old age and how should this be classified? Material and methods: A MEDLINE search in PubMed was conducted using the terms “epilepsy”, “elderly” and “incidence” or “prevalence” or “epidemiology” and relevant publications were analyzed. Results: The point prevalence of epilepsy of older age is 0.5–0.8% of the population and affects approximately 500,000 people in Germany. The highest age-adjusted prevalence is reported to lie beyond the age of 75 years. In recent decades, the prevalence climbed further among the 75-year-olds to be twice as high as among the adult working population. The incidence shows a significant increase among patients 65 years and older, reaches its maximum at around 80–85 years of age and is somewhat higher in men. Conclusion: Reasons for the high incidence and prevalence of epilepsy in old age are the age-related incidence of potentially epilepsy-associated diseases combined with a longer long-term survival for these diseases due to better medical care and an increase in life expectancy. The change in the age pyramid with a higher (and in the coming decades further increasing) proportion of old people, will further increase the rise of epilepsy of older age.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Aged; Elderly; Incidence; Prevalence; Seizures

Evaluation of simplified wireless EEG recordings in the neurological emergency room - Welte, Tamara; Janner, Felix; Lindner, Sara; Gollwitzer, Stephanie; Stritzelberger, Jenny; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (PLoS ONE, 2024)
Objective In the neurological emergency room (nER), timely electroencephalography (EEG) diagnostic is often crucial in patients with altered state of consciousness as well as in patients presenting with a first seizure. Yet, routine-EEG (rEEG) is often not available, especially during off-hours. Methods We analyzed the value of a commercially available, simplified wireless eight-channel EEG recording (swEEG, CerebAir® EEG headset, Nihon Kohden), applied by non-EEG-specialized medical students, in patients presenting in our nER with (suspicion of) epileptic seizures and/or loss of or altered state of consciousness between 08/2019 and 08/2022. We evaluated the feasibility and validity compared to a standard rEEG (21 electrodes according to the international 10/20 system) and also included the clinical follow-up of the patients. Results 100 patients were included in our analysis (mean age 57.6 ± 20.4 years; 61 male). Median time of electrode application was 7 minutes (range 4–20 minutes), with significantly longer duration in patients with altered level of consciousness (median 8 minutes, p = 0.035). Electrode impedances also differed according to state of consciousness (p = 0.032), and were higher in females (p<0.001). 55 patients received additional rEEG, either during their acute nER stay (25) and/or during the next days (38). Considering normal EEG findings vs. pathological slowing vs. epileptiform activity, swEEG matched first rEEG results in 48/55 cases (87.3%). Overall, swEEG detected the same or additional pathological EEG patterns in 52/ 55 cases (94.5%). In 7/75 patients (9.3%) who did not receive rEEG, or had their rEEG scheduled to a later time point during their hospital stay, swEEG revealed important additional pathological findings (e.g. status epilepticus, interictal epileptiform discharges), which would have triggered acute therapeutic consequences or led to further diagnostics and investigations. Conclusion The introduced swEEG represents a practicable, valuable technique to be quickly applied by non-EEG-specialized ER staff to initiate timely diagnostic and guide further investigations and treatment in the nER. Moreover, it may help to avoid under-diagnostic with potentially harmful consequences caused by skipped or postponed regular 10/20 EEG examinations, and ultimately improve the outcome of patients.
CRIS-Team Scopus Importer:2024-11-15

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

Hippocampal neurons code individual episodic memories in humans - Kolibius, Luca D.; Roux, Frederic; Parish, George; Ter Wal, Marije; Van Der Plas, Mircea; Chelvarajah, Ramesh; Sawlani, Vijay; Rollings, David T.; Lang, Johannes; Gollwitzer, Stephanie; Walther, Katrin; Hopfengärtner, Rüdiger; et al. (Nature Human Behaviour, 2023)
The hippocampus is an essential hub for episodic memory processing. However, how human hippocampal single neurons code multi-element associations remains unknown. In particular, it is debated whether each hippocampal neuron represents an invariant element within an episode or whether single neurons bind together all the elements of a discrete episodic memory. Here we provide evidence for the latter hypothesis. Using single-neuron recordings from a total of 30 participants, we show that individual neurons, which we term episode-specific neurons, code discrete episodic memories using either a rate code or a temporal firing code. These neurons were observed exclusively in the hippocampus. Importantly, these episode-specific neurons do not reflect the coding of a particular element in the episode (that is, concept or time). Instead, they code for the conjunction of the different elements that make up the episode.
CRIS-Team Scopus Importer:2023-10-20

Manufacturer switch of anti-seizure drugs may not increase the risk of seizure recurrence in Children: A nationwide study of prescription data in Germany - Lang, Johannes; Kostev, Karel; Reindl, Caroline; Müller, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Westermayer, Vivien; Trollmann, Regina; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: Several publications on the exchangeability of antiepileptic drugs in clinical settings revealed an increased risk for seizure recurrence after changing the manufacturer of anti-seizure drugs (ASD) in adults, possibly due to a decline of adherence. It is unclear whether this holds true in children and adolescents. Methods: Patient data of children and adolescents (<18 years) were collected anonymously from 236 German pediatricians and pediatric neurologists between January 2011 and December 2018 using the IMS® Disease Analyzer database (IQVIA, Frankfurt, Germany). Patients with epilepsy were included if at least 2 prescriptions within 360 days and 1 within 180 days prior to the index date were available. The cohort was separated into a seizure group and seizure-free controls. Both groups were matched 1:1 according to age, gender, insurance status, and treating pediatrician. The risk for seizure recurrence after a manufacturer switch of the same ASD at the last prescription before the index date was analyzed using a multivariate regression model. Results: A total of 678 children and adolescents with epilepsy were included (each group: n = 339; age: 9.6 ± 4.4 years). Comparing both groups, the risk for seizures recurrence was not increased after a manufacturer switch had occurred. Albeit changes during the last prescription before the index date had occurred more often in the seizure-free group, neither change of branded and generic products nor substances reached significance. Only change of ASD strength showed a significantly reduced odds ratio for seizures (OR 0.40, 95% CI 0.24–0.65, p < 0.001). Significance: In contrast to the available evidence in adults, changing the manufacturer did not appear to increase the risk for seizure recurrence in previously seizure-free children and adolescents with epilepsy.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Anti-seizure drugs; Manufacturer changes; Relapse seizures

Pre- and Postictal Changes in the Innate Immune System: Cause or Effect? - Lang, Johannes; Olmes, David G.; Proske, Manuel; Hagge, Mareike; Dogan Onugoren, Mujgan; Rothhammer, Veit; Schwab, Stefan; Hamer, Hajo (European neurology, 2021)
Introduction: Recent studies have shown that inflammatory processes might play a role in epileptogenesis. Their role in ictogenesis is much less clear. The aim of this study was to investigate peri-ictal changes of the innate immune system by analyzing changes of immune cells, as well as pro- and anti-inflammatory cytokines. Methods: Patients with active epilepsy admitted for video-EEG monitoring for presurgical evaluation were included. Blood was sampled every 20 min for 5 h on 3 consecutive days until a seizure occurred. After a seizure, additional samples were drawn immediately, as well as 1 and 24 h later. To analyze the different populations of peripheral blood mononuclear cells, all samples underwent FACS for CD3, CD4, CD8, CD56, CD14, CD16, and CD19. For cytokine analysis, we used a custom bead-based multiplex immunoassay for IFN-gamma, IL-1 beta, IL-1RA, IL-4, IL-6, IL-10, IL-12, IL-17, MCP-1, MIP-1 alpha, and TNF alpha. Results: Fourteen patients with focal seizures during the sampling period were included. Natural killer (NK) cells showed a negative correlation (rho = -0.3362, p = 0.0195) before seizure onset and an immediate increase to 1.95-fold afterward. T helper (T-H) and B cells decreased by 2 and 8%, respectively, in the immediate postictal interval. Nonclassical and intermediate monocytes decreased not until 1 day after the seizures, and cytotoxic T (T-C) cells showed a long-lasting postictal increase by 4%. IL-10 and MCP-1 increased significantly after seizures, and IL-12 decreased in the postictal phase. Discussion/Conclusion: Our study argues for a role of the innate immune system in the pre- and postictal phases. NK cells might be involved in preictal changes or be altered as an epiphenomenon in the immediate preictal interval.
CRIS-Team WoS Importer:2021-07-09

Psychogenic nonepileptic seizures: clinical characteristics and outcome - Volbers, Bastian; Walther, Katrin; Kurzbuch, Katrin; Erdmann, Laura; Gollwitzer, Stephanie; Lang, Johannes; Onugoren, Muejgan Dogan; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Brain and Behavior, 2022)
Background: Clinical characteristics, outpatient situation, and outcome in patients with psychogenic nonepileptic seizures (PNES) remain to be elucidated. Methods: Patients diagnosed with PNES after video-electroencephalography (EEG) monitoring (VEM) 03/2000–01/2016 at the Erlangen Epilepsy Center were surveyed between June 2016 and February 2017. Primary outcome was PNES cessation defined as no PNES episodes within > = 12 months prior to the interview. Secondary outcome variables included quality of life (QoL) and dependency. Sensitivity analysis included patients with proven PNES during VEM without comorbid epilepsy. Results: Ninety-nine patients were included (median age 38 (interquartile range (IQR 29–52)) years; 68 (69%) females, follow-up 4 (IQR 2.1–7.7) years). Twenty-eight (28%) patients suffered from comorbid epilepsy. Twenty-five (25%) patients reported PNES cessation. Older age at symptom onset (odds ratio (OR) related to PNES cessation: 0.95 (95% CI 0.90–0.99)), comorbid epilepsy (OR 0.16 (95% CI 0.03–0.83)), anxiety disorder (OR 0.15 (95% CI 0.04–0.61)), and tongue biting (OR 0.22 (95% CI 0.03–0.91)) remained independently associated with ongoing PNES activity after adjustment. Sensitivity analysis (n = 63) revealed depressive disorder (OR 0.03 (95% CI 0.003–0.34)) instead of anxiety as independent predictor, while this seemed relevant only in patients older than 26 years at onset (OR 0.04 (95% CI 0.002–0.78) versus OR 0.21 (95% CI 0.02–1.84) in patients younger than 26 years). PNES cessation was associated with increased median QoL (8 (IQR 7–9) versus 5.5 (IQR 4–7); p <.001) and an increased frequency of financial independency (14 (56%) versus 21 (28%); p =.01). Conclusions: We found poor outcomes in PNES especially in older patients at onset with comorbid depressive disorder. Comorbid epilepsy also seems to be a major risk factor of ongoing PNES activity, which in turn affects patients’ daily living.
CRIS-Team Scopus Importer:2022-04-22
Keywords: activities of daily living; mental disorders; nonepileptic seizures; patient-relevant outcome; prognosis

Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

The impact of the coronavirus disease (COVID-19) pandemic on outpatient epilepsy care: An analysis of physician practices in Germany - Müller, Tamara; Kostev, Karel; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Westermayer, Vivien; Reindl, Caroline; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: To gain insight into epilepsy care during coronavirus disease (COVID-19) pandemic, we analyzed prescription data of a large cohort of persons with epilepsy (PWE) during lockdown in Germany. Methods: Information was obtained from the Disease Analyzer database, which collects anonymous demographic and medical data from practice computer systems of general practitioners (GP) and neurologists (NL) throughout Germany. We retrospectively compared prescription data for anti-seizure medication (ASM) and physicians’ notes of “known” and “new” PWE from January 2020 until May 2020 with the corresponding months in the three preceding years 2017–2019. Adherence was estimated by calculating the proportion of patients with follow-up prescriptions within 90 days after initial prescriptions in January or February. We additionally analyzed hospital referrals of PWE. The significance level was set to 0.01 to adjust for multiple comparisons. Results: A total of 52,844 PWE were included. Anti-seizure medication prescriptions for known PWE increased in March 2020 (GP + 36%, NL + 29%; P < 0.01). By contrast, a decrease in prescriptions to known and new PWE was observed in April and significantly in May 2020 ranging from −16% to −29% (P < 0.01). The proportion of PWE receiving follow-up prescriptions was slightly higher in 2020 (73.5%) than in 2017–2019 (70.7%, P = 0.001). General practitioners and NL referred fewer PWE to hospitals in March 2020 (GP: −30%, P < 0.01; NL: −12%), April 2020 (GP: −29%, P < 0.01; NL: −37%), and May 2020 (GP: −24%, P < 0.01; NL: −16%). Conclusion: Adherence of known PWE to ASM treatment appeared to remain stable during lockdown in Germany. However, this study revealed findings which point to reduced care for newly diagnosed PWE as well as fewer hospital admissions. These elements may warrant consideration during future lockdown situations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Anti-seizure drugs; COVID-19; Epilepsy care

Theta rhythmicity governs human behavior and hippocampal signals during memory-dependent tasks - Ter Wal, Marije; Linde-Domingo, Juan; Lifanov, Julia; Roux, Frederic; Kolibius, Luca D.; Gollwitzer, Stephanie; Lang, Johannes; Hamer, Hajo; Rollings, David; Sawlani, Vijay; Chelvarajah, Ramesh; Staresina, Bernhard; et al. (Nature Communications, 2021)
Memory formation and reinstatement are thought to lock to the hippocampal theta rhythm, predicting that encoding and retrieval processes appear rhythmic themselves. Here, we show that rhythmicity can be observed in behavioral responses from memory tasks, where participants indicate, using button presses, the timing of encoding and recall of cue-object associative memories. We find no evidence for rhythmicity in button presses for visual tasks using the same stimuli, or for questions about already retrieved objects. The oscillations for correctly remembered trials center in the slow theta frequency range (1-5 Hz). Using intracranial EEG recordings, we show that the memory task induces temporally extended phase consistency in hippocampal local field potentials at slow theta frequencies, but significantly more for remembered than forgotten trials, providing a potential mechanistic underpinning for the theta oscillations found in behavioral responses.
CRIS-Team Scopus Importer:2021-12-17

Trends in the neurological emergency room, focusing on persons with seizures - Welte, Tamara; Ernst, Sebastian; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (European Journal of Neurology, 2023)
Background and purpose: Previous studies in neurological emergency rooms (nERs) have reported many non-acute, self-presenting patients, patients with delayed presentation of stroke, and frequent visits of persons with seizures (PWS). The aim of this study was to evaluate trends during the last decade, with special focus on PWS. Methods: We retrospectively analyzed patients who presented to our specialized nER during the course of 5 months in 2017 and 2019, and included information on admission/referral, hospitalization, discharge diagnosis, and diagnostic tests/treatment in the nER. Results: A total of 2791 patients (46.6% male, mean age 57 ± 21 years) were included. The most common diagnoses were cerebrovascular events (26.3%), headache (14.1%), and seizures (10.5%). Most patients presented with symptoms lasting >48 h (41.3%). The PWS group included the largest proportion of patients presenting within 4.5 h of symptom onset (171/293, 58.4%), whereas only 37.1% of stroke patients presented within this time frame (273/735). Self-presentation was the most common admission pathway (31.1%), followed by emergency service referral (30.4%, including the majority of PWS: 197/293, 67.2%). Despite known diagnosis of epilepsy in 49.2%, PWS more often underwent accessory diagnostic testing including cerebral imaging, compared to the overall cohort (accessory diagnostics 93.9% vs. 85.4%; cerebral imaging 70.1% vs. 64.1%). Electroencephalography in the nER was only performed in 20/111 patients (18.0%) with a first seizure. Nearly half of the patients (46.7%) were discharged home after nER work-up, including most self-presenters (632/869, 72.7%) and headache patients (377/393, 88.3%), as well as 37.2% (109/293) of PWS. Conclusion: After 10 years, nER overuse remains a problem. Stroke patients still do not present early enough, whereas PWS, even those with known epilepsy, often seek acute and extensive assessment, indicating gaps in pre-hospital management and possible over-assessment.
CRIS-Team Scopus Importer:2023-09-15
Keywords: epilepsy; headache; neurological emergency room; seizures; stroke